2016
DOI: 10.1080/10503307.2015.1132857
|View full text |Cite
|
Sign up to set email alerts
|

Competence feedback improves CBT competence in trainee therapists: A randomized controlled pilot study

Abstract: Competence feedback was demonstrated to be suitable for the improvement of therapeutic competencies in CBT. These findings may have important implications for psychotherapy training, clinical practice, and psychotherapy research. However, further research is necessary to ensure the replicability and generalizability of the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 33 publications
3
29
0
4
Order By: Relevance
“…Furthermore, different competence scales might provide more insight into the processes involved in successful treatment, which could help to identify the most important therapeutic skills and integrate them into therapist training and education. The use of competence rating scales to give therapists specific feedback improves therapeutic competence more than regular supervision, as shown in a study by Weck, Kaufmann, and Höfling (2016). Furthermore, different competence scales might be helpful for monitoring the dissemination of information in treatment manuals because they allow to determine which therapeutic competence will improve after treatment training.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different competence scales might provide more insight into the processes involved in successful treatment, which could help to identify the most important therapeutic skills and integrate them into therapist training and education. The use of competence rating scales to give therapists specific feedback improves therapeutic competence more than regular supervision, as shown in a study by Weck, Kaufmann, and Höfling (2016). Furthermore, different competence scales might be helpful for monitoring the dissemination of information in treatment manuals because they allow to determine which therapeutic competence will improve after treatment training.…”
Section: Discussionmentioning
confidence: 99%
“…This is a key characteristic of training supervision, and its quick reduction post-qualification is noteworthy as therapists have higher and more complex caseloads. Only 1/7 non-competent therapists reported that supervision included feedback on audio recordings of therapy, possibly indicating the usefulness of ongoing review and feedback of actual therapy sessions after initial training (Bearman et al 2017;Weck et al 2017); however, competent and non-competent therapists did not differ significantly in post-training access to live supervision or in frequency of supervision overall. Small numbers and the lack of a control condition make conclusions difficult.…”
Section: Clinical Role and Supervisionmentioning
confidence: 97%
“…Considering these findings, other perspectives should be taken into account as well. Comparisons to supervisor perceptions or assessment of therapeutic competencies and behavior by independent raters (Dennhag, Gibbons, Barber, Gallop, & Crits-Christoph, 2012, Weck, Kaufmann, & Höfling, 2016) could be methodologically useful. It should be noted that outcome measurement is a significant challenge in supervision research in general, with no universal agreement prevailing on what constitutes a positive outcome (Palomo, Beinart, & Cooper, 2010).…”
Section: Slqmentioning
confidence: 99%